Política e tecnologia através da cor: a controvérsia em torno do Vantablack - Campagnaro, Yuri Gabriel (2024)
The subject of this research is the controversies around Vantablack, a nanotechnology coating that has the optical effect of low light reflectivity, exclusively appropriated for artistic purposes by artist Anish Kapoor, which is combatted by the action of Stuart Semple. This thesis uses the methodology of sociotechnical controversies cartography (Tommaso Venturini), identifying its primary and secondary actors, as well as the disputed issues. In a multidisciplinary approach, theories from the field of Science, Technology and Society are combined, with Material Culture, Color Theory, art and philosophy to make critical considerations about the co-production between art, technoscience and politics. We consider the materialities of colors and their agencies and identify an ontological multiplicity in Vantablack, which acts in its different natures of material, color and paint, in associations and conflicts. We conclude that there is an important mediation of artistic poetics with technology and politics, activated in the relationship between different worlds and actors.